PROTECTION OF THE WIFE AS A VICTIM OF CRIME IN DOMESTIC VIOLENCE: (Study in Police Resort Blitar) - Cindy Tiara Gracia Yoseph; Teguh Suratman; Riski Febria Nurita (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2022)
Domestic violence is an unlawful act, and if it is specifically regulated by the Criminal Code or a particular law, it can be classified as a criminal offense. This study focuses on the "Protection against Victims of Domestic Violence (Blitar Regency Resort Police Study)." The research problem is formulated as follows: How is the legal protection of victims of domestic violence crimes by the Blitar Resort Police, and what obstacles do they face in providing such legal protection. Empirical research methods were used to collect data, and the research was conducted at the Blitar Resort Police. In-person interviews with the organizational structures in the Blitar Resort Police served as the primary data source. Secondary data sources include Article 351 of the Criminal Code, which defines abuse in physical and verbal forms, and Law No. 23 of 2004 on the Elimination of Domestic Violence. Additionally, legal books, legal journals, legal writings, and the perspectives of jurists were used as tertiary data sources. The data analysis utilized qualitative descriptive techniques, leading to the research findings at the Blitar Resort Police. The legal protection efforts included preventive measures and repressive actions. Preventive efforts involved following up on reports or complaints of domestic violence and conducting awareness campaigns. Repressive efforts included taking legal action against domestic violence perpetrators and providing full legal assistance to domestic violence victims. The main obstacles faced by the Blitar Police were the victims' reluctance to immediately report domestic violence cases to the police and the perpetrators' tendency to escape, which hindered the investigative process.